Respuesta :
Answer:
Step-by-step explanation:
x
+
2
y
=
6
Subtract
x
from both sides of the equation.
2
y
=
6
−
x
Divide each term by
2
and simplify.
Tap for more steps...
y
=
3
−
x
2
Answer:
x=2y-6
Step-by-step explanation:
To solve for x, we need to have one more equation, as there are two variables; x and y. But, we can still get it to this point.
First, we need to get x on to one side.
x=-2y-6
That is all we can do from here.
If you provide another corresponding equation, we can solve for x.
Hope this provides some guidance!!
~gloriouspurpose~